A STUDY OF LOAD TRANSFER MECHANISM OF PILE IN SEDIMENT SOILS USING 3D FINITE ELEMENT METHOD (CASE STUDY: DERMAGA KIJING, MEMPAWAH, WEST KALIMANTAN) - Granita Wuri Bemby, Wafi
There are many cases where the piles are on soils that are dominated by soft soil or in soil conditions where the soft clay soil is thick enough and the hard soil is at a deep depth. In this soil condition, the pile needs to be driven through the soft soil layer to a certain depth. Most of the resistance of these piles came from skin friction so that these piles were called friction piles. However, in the course of designing, it was impossible to classify a layer of soil as clay without containing sand at all and the other way around. We need to consider all possible behaviors. For example, a soil layer was classified as clayey sand, then how to represent it in design calculations, especially in long-term behavior, such as consolidation settlement. This might not have an effect for small scale constructions, but this would have a dangerous effect for large-scale constructions. Therefore, the accuracy of the prediction of settlement in the pile group would be very crucial. In this research the soil interaction of a pile system in sandy clay and loose sand was investigated. This study utilized the professional finite element software Plaxis 3D to investigate the load transfer mechanism and settlement of a single and group pile system. Available site test results of the new international port in Mempawah were used, such as Bore Log, PDA Test, PDR Test, and Static Loading Test. The soil parameters used in the analysis were based on available soil test data as well as several empirical correlations that have been widely accepted in academia and in the practical world. The analysis was carried out with soil conditions dominated by clay to a depth of -60 m with a layer of soil at a depth of -29 m to -41 m classified in two conditions, considered as sandy clay and considered as loose sand. Based on this study’s outcomes, load distribution was influenced by soil consistency. The piles received all applied load until the ultimate capacity of the piles was exceeded. Piles in sand carried greater load than piles in clay. Pore pressure can be dissipated better in soil with a layer of sand. The analysis results showed that differences in soil classification can lead to differences in settlement predictions. The soil layer that was considered as clay has greater consolidation settlement value and has different pattern with the soil layer that was considered as sand. Therefore, the reinforcement of the upper structure will be different. The increase of settlement can be affected by number, soil layer, and consistency of the bearing layers.